2003
DOI: 10.1590/s0103-90162003000400027
|View full text |Cite
|
Sign up to set email alerts
|

Cold storage of 'Tahiti' lime treated with 1-methylcyclopropene

Abstract: The storage of 'Tahiti' limes under low temperatures enables the extension of the commercialization period. However the loss of the skin green color and the occurrence of chilling injuries prevent such advantage. The purpose of this work was to verify the efficiency of 1-methylcyclopropene (1-MCP), an inhibition of ethylene action, during the cold storage of 'Tahiti' lime. Fruits were treated for 12 hours with 1-methylcyclopropene at concentrations of 0 or 1.0 µL L -1 and then were stored at 5 or 10 o C for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
3
9
0
2
Order By: Relevance
“…As expected, in contrast to ethylene, the most pronounced effect of 1-MCP during postharvest storage of citrus is inhibition of fruit degreening, and retention of the peel green color, a phenomenon that has been observed in various citrus species, including orange, grapefruit and lime (Porat et al, 1999;Jomori et al, 2003;McCollum and Maul, 2007). This effect of 1-MCP on inhibition of peel degreening is especially beneficial for lime fruits, which are required to retain their green color during storage and marketing, therefore 1-MCP can assist in retention of their external quality Kluge et al, 2003).…”
Section: Citrussupporting
confidence: 67%
See 1 more Smart Citation
“…As expected, in contrast to ethylene, the most pronounced effect of 1-MCP during postharvest storage of citrus is inhibition of fruit degreening, and retention of the peel green color, a phenomenon that has been observed in various citrus species, including orange, grapefruit and lime (Porat et al, 1999;Jomori et al, 2003;McCollum and Maul, 2007). This effect of 1-MCP on inhibition of peel degreening is especially beneficial for lime fruits, which are required to retain their green color during storage and marketing, therefore 1-MCP can assist in retention of their external quality Kluge et al, 2003).…”
Section: Citrussupporting
confidence: 67%
“…Therefore, several studies evaluated the potential aplication of 1-MCP for prevention of CI and decay, but they have yielded conflicting findings. In the case of CI, some reports indicated that exposure to 1-MCP reduced CI development (Dou et al, 2005;Salvador et al, 2006;Edagi et al, 2010), whereas others showed no effect or even some enhancement of CI (Porat et al, 1999;Kluge et al, 2003;Jomori et al, 2003). In the case of decay development, some studies found that 1-MCP reduced decay (Edagi et al, 2010) whereas others indicated that 1-MCP rather increased decay rates (Porat et al, 1999;Dou et al, 2005).…”
Section: Citrusmentioning
confidence: 99%
“…Ethylene-induced degreening is completely inhibited by pre-treatment with 1-MCP (Fig. 1A; Jomori et al ., 2003; McCollum and Maul, 2007; Li et al ., 2016). 1-MCP treatment also inhibits the ripening process in fruit that have a strong requirement for ethylene to ripen (Watkins, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…They were directly transferred, individually, on the same day to the Biophysical and Biological laboratory of Ferdowsi University of Mashhad (longitude: 59°38′E and latitude: 36°16′N), Iran. The best conditions for keeping lime are temperature ranging from 10-12°C and relative humidity of 85-95 % (Jomori et al 2003). For ignoring the effect of environmental parameters, the samples were kept in these conditions for 24 h. The cut parts of the fruits were weighed and dried in an oven at a temperature of 80°C for 74 h and then the weight lost on drying to reach the final content weight was recorded as moisture content (AOAC 1984).…”
Section: Methodsmentioning
confidence: 99%